Small bowel obstruction from hollow foreign body ingestion: A case report and brief review of literature - Crain, Matthew A. (Radiol Case Rep, 2021)
While ingestion of a foreign body by children is common, diagnosis is often challenging, especially when the consumption by a young child is unwitnessed and presenting symptoms mimic other medical conditions. If the foreign body does not pass spontaneously, radiological imaging studies are typically performed, but visualization and identification of the ingested foreign object can be inconclusive, especially when an unidentified mass is radio translucent. Under this circumstance, physicians often have to go on a “fishing expedition”, using exploratory endoscopy and/or surgery to identify and extract the object that became lodged. In this report we discuss a case of a 3 year-old boy who presented with abdominal pain and signs of bowel obstruction. Imaging revealed an ingested “radiolucent” foreign body, masqueraded as soft-tissue mass and enteric duplication cyst, delaying the diagnosis. Systematic shape and density reanalysis of CT and US imaging suggested a hollow object lodged at the terminal ileum. The patient underwent exploratory laparotomy with extraction of a hollow toy “fish”. There is a dearth of literature regarding hollow ingested objects. This case report highlights the importance of systematic density and shape imaging analyses in order to identify and locate hollow ingested objects.